Cancer Causing Substances - Atroshi, Faik (IntechOpen, 2018)
Cancer risk factors include exposure to certain substances, which may contribute to the development of cancer. However, substances can have different levels of cancer-causing potential, and the risk of developing cancer is dependent on several factors, including individual genetic background and the amount and duration of the exposure. This book focuses on various cancer risk factors, covering numerous known, probable, and possible carcinogens; their role in carcinogenesis; mechanisms of carcinogenicity; and methods for detecting carcinogens. And due to the growing concerns over the effects that substances and environmental exposures can have on human health, the chapters also emphasize on the vital need for further topic-related research as well as development and implementation of beneficial approaches.